From overtourism to overall-mobility - José Antonio Donaire Benito; Konstantina Zerva (Annals of Tourism Research Empirical Insights, 2025)
Drawing from the New Mobility Paradigm, tourist cities embody more complexity than mere dichotomies of 'hosts' versus 'guests.' They are the result of multiple users of urban space overlapping in a highly mobile and hyper-nomadic society. By combining mobile positioning-based data, various official surveys, and the interpolation of census data, this article measures the relative weight of the different users of the city of Barcelona in 2019 and their distribution both temporally and spatially. Results indicate that the absolute value of different types of visitors is much higher than official data suggest, but their relative value is conditioned by the high volume of other forms of mobility. The tension between users generates very diverse spatial responses, ranging from coexistence to exclusion.
Keywords: 330; Barcelona; New mobilities paradigm; Overall-mobility; Overtourism; Spatio-temporal behavior